Patients with symptoms of haemolytic anaemia and thrombocytopenia revealed by genetic testing as sitosterolemia - Mengjia Qian; Pu Chen; Yanxia Zhan; Bijun Zhu; Lingyan Wang; Miaomiao Zhang; Yujie Zhou; Hao Chen; Lili Ji; Yunfeng Cheng (Clinical and Translational Discovery)
Abstract Background Sitosterolemia is a rare, inherited, autosomal recessive disorder of lipid metabolism. Patients with sitosterolemia may exhibit diverse, distinct clinical characteristics. Methods and results We report cases of sitosterolemia with haematological abnormalities as primary initial symptoms. Both patients were seen with symptoms of haemolytic anaemia and thrombocytopenia. Their plasma levels of low‐density lipoprotein‐cholesterol were normal. Genetic tests were arranged as stomatocytes were found in their peripheral blood smears. Three heterozygous mutations in adenosine triphosphate‐binding cassette subfamily G member 5 (ABCG5) were identified in case 1. A mutation in integrin beta 3 was discovered in case 2, while no mutations were found in ABCG5 or ABCG8. Sitosterolemia was considered for both cases, and Ezetimibe was used for treatment, with quick curative responses. Conclusion For patients with unexplained haemolytic anaemia, thrombocytopenia, especially with stomatocytes present in peripheral blood, the diagnosis of sitosterolemia should be considered, and genetic testing is recommended.